Hypocrellin B-based activatable photosensitizers for specific photodynamic effects against high H2O2-expressing cancer cells. Issue 2 (1st December 2021) - Kitamura, Takashi; Nakata, Hirotaka; Takahashi, Daisuke; Toshima, Kazunobu
Abstract : A purpose-designed synthetic H2 O2 -activatable photosensitizer 4 based on hypocrellin B (3 ) exhibited selective photo-cytotoxicity against target cancer cells upon photo-irradiation with highly tissue penetrating 660 nm light. Abstract : A novel tumor-related biomarker, a H2 O2 -activatable photosensitizer 4 based on the 1, 3-dicarbonyl enol moieties of hypocrellin B (3 ), was designed and synthesized. The photosensitizer 4 showed a blue-shifted absorption band compared with 3, and showed negligible photosensitizing ability without H2 O2 . However, the release of 3 from 4 by the reaction with H2 O2 regenerated the photosensitizing ability. Furthermore, 4 exhibited selective and effective photo-cytotoxicity against high H2 O2 -expressing cancer cells upon photo-irradiation with 660 nm light, which is inside the phototherapeutic window.